Dislocation dynamics formulation for self-climb of dislocation loops by vacancy pipe diffusion. (September 2019) - Niu, Xiaohua; Gu, Yejun; Xiang, Yang
Abstract: It has been shown in experiments that self-climb of prismatic dislocation loops by pipe diffusion plays important roles in their dynamical behaviors, e.g., coarsening of prismatic loops upon annealing, as well as the physical and mechanical properties of materials with irradiation. In this paper, we show that the dislocation dynamics self-climb formulation that we derived in (Niu et al., 2017) is able to quantitatively describe the properties of self-climb of prismatic loops that were observed in experiments and atomistic simulations. This dislocation dynamics formulation applies to self-climb by pipe diffusion for any configurations of dislocations, and is able to recover the available models in the literature for rigid self-climb motion of small prismatic loops. We also present implementation method of this self-climb formulation. Simulations performed show evolution, translation and coalescence of prismatic loops as well as prismatic loops driven by an edge dislocation by self-climb motion and the elastic interaction between them. These results are in excellent agreement with available experimental and atomistic results. We have also performed systematic analyses of the behaviors of a prismatic loop under the elastic interaction with an infinite, straight edge dislocation by motions of self-climb and glide. Highlights: Our DDD formulation for self-climb by pipe diffusion quantitatively describes the results of experiments and atomistic simulations. Our DDD model gives pointwise self-climb velocity, and recovers the available models for rigid self-climb motion of small prismatic loops. A DDD implementation method of this self-climb formulation is presented, which is easily incorporated within the available methods and codes. Systematically analyzed behaviors of a prismatic loop under the elastic interaction with an edge dislocation by motions of self-climb and glide.